Procedimentos para gestão de ocorrência de inundações em cidades de pequeno e médio portes com o uso de SIG e logística humanitária. Estudo de caso: cidade de Jahu, SP - Feltrin, Talita Fernanda (Universidade Federal de São Carlos, 2014)
The scenarios of natural disasters are a reality today, and tend to become increasingly frequent in view of climate change that generate abnormal conditions intensively, since the increase of people living without adequate infrastructure susceptible to the ocurrence of disaster areas, even increasing number of vehicles on the streets, which may cause and/or exacerbate the intensity of disasters. In Brazil, municipalities suffer from landslides, strong winds, drought and floods mainly. Through emergency situations, the logistics network is fundamental to manage the supplies should be stored in strategic locations and care teams should be positioned near the sites affected by the disaster and may meet in a timely manner, especially sites that were affected with greater intensity. In view of this, it is necessary, through the use of Geographic Information System (GIS) map areas of risk, define and quantify the strategic points that will support the management of the Humanitarian Logistics, in order to ensure lower response time, minimize risk, and optimal performance in cases of emergency contingencies. Based on these aspects, this research aimed to develop a method of disaster management, by analyzing the areas of floods risk, through a Geographic Information System, seeking to identify, from this mapping, the locations that serve as supply warehouses and central of assistance for care teams. GIS, as well as LSS (Logistics Support System), tool that was used in this research, assisted in the preparation of the flow procedures for the logistics management of flooding for small and medium cities. Through simulations, could observe that for the case of a mapping realized using models and mathematical methods and due to lack of data registered along the basin studies, that was used the Method Muskingum-Cunge that best applied to types of data collected. Whit this, the study focused only on the river macrodrainage Jahu. To determine the strategic locations were considered urban facilities such as schools, kindergartens, hospitals, and others to act as local shelters and warehouses for humanitarian assistance. With the use of LSS could be analyzed that the tool allows organizing, quantify and qualify supplies received and distributed, to avoid the lack of essential surpimentos unnecessary and excessive supplies. Finally, from the use of LSS and GIS tools as well as the development of procedures for the management of humanitarian logistics is possible prepare the contingency plan for the occurrence of flooding to attend the Federal Law 12,608, with the main objective to reduce the time of decision making by Civil Defense and service teams.
Keywords: Planejamento urbano; Inundações; Logística humanitária; Procedimentos operacionais; Sistemas de informação geográfica; Ferramenta de apoio à logística; SIG; LSS; Floods; Humanitarian logistics; Proceedings; ENGENHARIAS